3D bioprinted colorectal cancer models based on hyaluronic acid and signalling glycans. (15th February 2023) - Cadamuro, Francesca; Marongiu, Laura; Marino, Michele; Tamini, Nicolò; Nespoli, Luca; Zucchini, Nicola; Terzi, Alberta; Altamura, Davide; Gao, Zirui; Giannini, Cinzia; Bindi, Greta; Smith, Andrew; et al.
Abstract: In cancer microenvironment, aberrant glycosylation events of ECM proteins and cell surface receptors occur. We developed a protocol to generate 3D bioprinted models of colorectal cancer (CRC) crosslinking hyaluronic acid and gelatin functionalized with three signalling glycans characterized in CRC, 3′-Sialylgalactose, 6′-Sialylgalactose and 2′-Fucosylgalactose. The crosslinking, performed exploiting azide functionalized gelatin and hyaluronic acid and 4arm-PEG-dibenzocyclooctyne, resulted in biocompatible hydrogels that were 3D bioprinted with commercial CRC cells HT-29 and patient derived CRC tumoroids. The glycosylated hydrogels showed good 3D printability, biocompatibility and stability over the time. SEM and synchrotron radiation SAXS/WAXS analysis revealed the influence of glycosylation in the construct morphology, whereas MALDI-MS imaging showed that protein profiles of tumoroid cells vary with glycosylation, indicating that sialylation and fucosylation of ECM proteins induce diverse alterations to the proteome of the tumoroid and surrounding cells. Graphical abstract: Unlabelled Image